A FEA Method for Deformation Characteristics of Circular Cylindrical Shells Compressed by Two Rigid Plates. Issue 4 (July 2021) - Zhang, Ziqian; Yang, Huilin; Zhao, Fei; Jiang, Nianshun
Abstract: Circular cylindrical thin shells as one of the most energy absorbing elements are used in various engineering applications. One of the most important applications is compressing shells laterally between two rigid plates. Many researchers have work on this issue, but it is hard to be analyzed by the theoretical methods. In the present paper, a finite element model was developed to resemble the compressive process of circular cylindrical shell by two rigid plates laterally. Then a dynamic simulation was carried out using ANSYS LS-DYNA program. The cross-sectional profile and Mises stress distributions as well as the load–displacement curve was obtained by the FEA process, which can reveal the main deformation characteristics of circular cylindrical shells compressed between two rigid plates.